2020
DOI: 10.3390/jcm9010147
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Study of a B Cell-Based and Monocyte-Based Immunotherapeutic Vaccine, BVAC-C in Human Papillomavirus Type 16- or 18-Positive Recurrent Cervical Cancer

Abstract: BVAC-C is a B cell-based and monocyte-based immuno-therapeutic vaccine transfected with a recombinant human papillomavirus (HPV) 16/18 E6/E7 gene and loaded with alpha-galactosyl ceramide, which is a natural killer T cell ligand. This phase I study sought to determine the tolerability and immunogenicity of BVAC-C in platinum-resistant recurrent cervical cancer patients. Patients with HPV 16-positive or 18-positive recurrent or persistent cervical cancer who had received at least one prior platinum-based combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 21 publications
(29 reference statements)
0
12
0
Order By: Relevance
“…However, there are no confirmed molecular markers for tumour progression or prognosis in CC patients. The related viral proteins E6 and E7 have been the focal points of research for the past several years [11,12]. In other words, easily detectable and meaningful molecular markers need to be confirmed.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are no confirmed molecular markers for tumour progression or prognosis in CC patients. The related viral proteins E6 and E7 have been the focal points of research for the past several years [11,12]. In other words, easily detectable and meaningful molecular markers need to be confirmed.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 25 trials were identified assessing therapeutic vaccines in cervical cancer patients [ 21 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ], of which 4 were not specific to cervical cancer but included a larger population with various cancers. The trials were published between 1989 and 2020.…”
Section: Resultsmentioning
confidence: 99%
“…Immunologic response analysis showed that BVAC-C induced activation of natural killer T cells, natural killer cells, and HPV E6/ E7 specific CD4 and CD8 T cells upon vaccinations in all patients evaluated. A phase II study is underway [36], as it is a phase I study of BVAC-B, transfected with recombinant HER2/neu, in patients with gastric cancer [37].…”
Section: Oncogenic Viral Antigensmentioning
confidence: 99%